The Influence of Physical Attractiveness, Social Attractiveness and Attitude Homophily towards the Credibility of Travel Vlogger - Eko Sigit Pramudito; Nosica Rizkalla; Purnamaningsih Purnamaningsih (Formosa Journal of Sustainable Research, 2022)
The COVID-19 pandemic has caused a decline in the Indonesian economy, including the tourism sector. As the condition has been improving in 2021, several strategies have been initiated to restore consumer interest in visiting tourist attractions. One of the ways is by collaborating with travel vloggers or travel influencers to promote tourist attractions. However, in-depth consideration is needed in the selection of the representative travel vlogger. The chosen figure must be credible so that the results of the review or recommendation can be trusted by consumers. This study aims to examine whether attitude homophily, physical attractiveness and social attractiveness can affect the credibility of a travel vlogger or travel influence. Based on the results of the multiple regression analysis, it is evident that the three proposed factors have a significant effect on the credibility of travel vloggers or travel influencers